Canine parvovirus: where are we in the 21st Century?. Issue 4 (11th June 2013) - Bird, Louise; Tappin, Simon
<x xml:space="preserve">Abstract</x> Canine parvovirus (CPV) is still a significant cause of viral enteritis in the dog and associated with high levels of mortality in untreated animals. Viral replication in the intestinal mucosa leads to melaenic and haemorrhagic diarrhoea, which results in hypovolaemic shock. This is followed by progressive sepsis as a result of intestinal bacterial translocation, and neutropenia secondary to viral replication within the bone marrow. Aggressive treatment with intravenous fluid therapy, anti‐emetics and antibiosis leads to improvement and recovery in most cases. More aggressive treatment including early nutritional intervention and interferon can improve outcome. Vaccination is protective in the majority of cases, although vaccine failure can occur if there is interference by materially‐derived antibodies.